Genomic insights into the uncultivated marine Zetaproteobacteria at Loihi Seamount - Field, Erin K; Sczyrba, Alexander; Lyman, Audrey E; Harris, Christopher C; Woyke, Tanja; Stepanauskas, Ramunas; Emerson, David (ISME JOURNAL, 2015)
The Zetaproteobacteria are a candidate class of marine iron-oxidizing bacteria that are typically found in high iron environments such as hydrothermal vent sites. As much remains unknown about these organisms due to difficulties in cultivation, single-cell genomics was used to learn more about this elusive group at Loihi Seamount. Comparative genomics of 23 phylogenetically diverse single amplified genomes (SAGs) and two isolates indicate niche specialization among the Zetaproteobacteria may be largely due to oxygen tolerance and nitrogen transformation capabilities. Only Form II ribulose 1,5-bisphosphate carboxylase (RubisCO) genes were found in the SAGs, suggesting that some of the uncultivated Zetaproteobacteria may be adapted to low oxygen and/or high carbon dioxide concentrations. There is also genomic evidence of oxygen-tolerant cytochrome c oxidases and oxidative stress-related genes, indicating that others may be exposed to higher oxygen conditions. The Zetaproteobacteria also have the genomic potential for acquiring nitrogen from numerous sources including ammonium, nitrate, organic compounds, and nitrogen gas. Two types of molybdopterin oxidoreductase genes were found in the SAGs, indicating that those found in the isolates, thought to be involved in iron oxidation, are not consistent among all the Zetaproteobacteria. However, a novel cluster of redox-related genes was found to be conserved in 10 SAGs as well as in the isolates warranting further investigation. These results were used to isolate a novel iron-oxidizing Zetaproteobacteria. Physiological studies and genomic analysis of this isolate were able to support many of the findings from SAG analyses demonstrating the value of these data for designing future enrichment strategies.
Keywords: ROV Jason (Remotely Operated Vehicle)